Performance Spaces and Stage Technologies : a Comparative Perspective on Theatre History - Nawata, Yūji, 1964-; Nawata, Yūji, 1964-; Dethlefs, Hans Joachim; Dethlefs, Hans Joachim; Soichiro, Itoda; Takayuki, Hioki; Tatsuhiko, Seo; Van Eikels, Kai; Yasuko, Enomoto; Yasuyuki, Mitsuma; Yuichi, Ishida; Yuji, Nawata (Theater (Transcript (Firm)), 2022)
The history of theatre has often been written as a history of great writers, actors, or directors. This book takes a different approach: the contributors examine the history of performance from the perspective of theatre spaces and stage technologies. Art, literature, religion, law, urbanism, architecture, technology - this interdisciplinary book discusses how these fields relate to theatre and performance. Geographically, it covers a significant portion of the globe; chronologically, it ranges from ancient times to the present. This book provides a timely attempt to combine cultural and global history.